Akurasi Pemeriksaan Potong Beku Dibandingkan dengan Histopatologi untuk Mendiagnosis Tumor Ovarium di RSUP Sanglah Denpasar - Ida Ayu, Priandini; Dewi, I Gusti Ayu Sri Mahendra; Winarti, Ni Wayan; Sriwidyani, Ni Putu (E-Jurnal Medika Udayana; Vol 12 No 11 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i11.P08, 2023)
Ovarian tumors are gynecological tumors that are difficult to detect because of the variety of symptoms and signs that require a precise and accurate diagnosis. Frozen section examination is a histological examination performed rapidly in intraoperative cases in the diagnosis of ovarian tumors with paraffin block examination as the gold standard. This study aims to assess the accuracy of frozen section compared to histopathological examination of paraffin blocks in diagnosing ovarian tumors in RSUP Sanglah Denpasar. This study is a diagnostic test study with a sample of 62 patients selected by consecutive sampling method. Value of sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were calculated from the sample obtained. On paraffin blocks examination, 36 cases of benign ovarian tumors (benign and borderline neoplasms) and 26 cases of malignant ovarian tumors were found. This study obtained a sensitivity value of 88.5%, specificity 100%, positive predictive value 100%, negative predictive value 92.3%, and frozen section accuracy value 95.2%. Therefore, the frozen section examination is a good diagnostic test tool to be used in the diagnosis of ovarian tumors. Keywords : Paraffin Block, Frozen Section, Ovarian Tumor. Tumor ovarium merupakan tumor ginekologi yang sulit dideteksi karena gejala dan tanda yang beragam sehingga memerlukan cara diagnosis yang tepat dan akurat. Pemeriksaan potong beku merupakan pemeriksaan histologi yang dilakukan secara cepat dalam kasus intraoperatif pada diagnosis tumor ovarium dengan pemeriksaan histopatologi blok parafin yang menjadi standar baku emas. Penelitian bertujuan untuk menilai akurasi dari alat uji diagnostik potong beku dengan pemeriksaan histopatologi blok parafin untuk mendiagnosis tumor ovarium di RSUP Sanglah Denpasar. Penelitian ini merupakan penelitian uji diagnostik dengan jumlah sampel 62 pasien yang dipilih dengan metode consecutive sampling . Pada sampel dihitung nilai sensitivitas, spesifisitas, nilai prediksi positif, nilai prediksi negatif, dan akurasi. Pada pemeriksaan histopatologi blok parafin ditemukan 36 kasus tumor ovarium jinak (neoplasma jinak dan borderline) dan 26 kasus tumor ovarium ganas. Penelitian ini mendapatkan nilai sensitivitas 88,5%, spesifisitas 100%, nilai prediksi positif 100%, nilai prediksi negatif 92,3%, dan nilai akurasi potong beku 95,2%. Berdasarkan hal tersebut, pemeriksaan potong beku merupakan alat uji diagnostik yang baik untuk digunakan dalam penegakan diagnosis tumor ovarium. Kata kunci :  Blok Parafin, Potong Beku, Tumor Ovarium.